The Structure of Local Public Finance and the Quality of Life - Gyourko, Joseph; Tracy, Joseph (Journal of Political Economy, 1991)
Differences in local fiscal conditions generate compensating differentials across local land and labor markets just as we have long known amenities to do. Thus the fiscal climate affects the quality of life across metropolitan areas. We present new results showing that intercity fiscal differentials are nearly as important as amenity differentials in determining the quality of life across urban areas. The paper also investigates the sensitivity of the quality-of-life rankings with respect to assumptions about the nature of the marginal entrant. We estimate a random effects model to account for city-specific error components in the housing and wage regressions. Those results indicate that the standard errors of previous OLS-based quality-of-life rankings have been biased downward substantially. More encompassing data on city traits as well as superior controls for worker and housing quality are needed to increase the precision of quality-of-life estimates.